Catalpa speciosa water-holding capacity study in Karaganda and Zhezkazgan - Tleukenova, S.U.; Gavrilkova, E.A.; Madiyeva, A.N.; Matveev, A.N.; Aitymov А.К. (Fundamental and Experimental Biology, 2022)
The study of the hydration and water-retaining capacity of plant leaves is important for assessing the possibil-ity of their cultivation and mass use in green construction in the arid conditions of Kazakhstan. This article examines the issues of hydration and water-retaining capacity of the leaves of the valuable ornamental culture Catalpa speciosa in the conditions of the cities of Karaganda and Zhezkazgan. The indicators of hydration and weight loss during drying for 1, 3 and 6 hours were studied by leaves of plants of the 1st, 2nd and 3rd years of vegetation from May to August. It was found that the leaves of Catalpa speciosa in the conditions of the city of Karaganda had higher indicators of hydration and water-holding capacity than in the city of Zhezkazgan. The maximum values of moisture loss during drying were noted for plants of the 1 st year of veg-etation, the minimum values for individuals of the 3 rd year. By the months of the vegetative season, the leaves lose free water as much as possible in the conditions of Karaganda in June, for Zhezkazgan in June and July; minimal moisture losses were noted for both cities — in August. Thus, critical points of water exchange in-tensity were identified in June and July, which require intensification of irrigation in these months. More active watering must be organized for plants in the 1st year of development. In general, good indicators of the water-holding capacity of Catalpa speciosa leaves have been established, which indicates the possibility of active use of this crop in the green construction of arid territories of Central Kazakhstan.